Consensus statement on mandatory measurements in pancreatic cancer trials (COMM-PACT) for systemic treatment of unresectable disease. Issue 3 (March 2018) - ter Veer, Emil; van Rijssen, L Bengt; Besselink, Marc G; Mali, Rosa M A; Berlin, Jordan D; Boeck, Stefan; Bonnetain, Franck; Chau, Ian; Conroy, Thierry; Van Cutsem, Eric; Deplanque, Gael; Friess, Helmut; et al.
Summary: Variations in the reporting of potentially confounding variables in studies investigating systemic treatments for unresectable pancreatic cancer pose challenges in drawing accurate comparisons between findings. In this Review, we establish the first international consensus on mandatory baseline and prognostic characteristics in future trials for the treatment of unresectable pancreatic cancer. We did a systematic literature search to find phase 3 trials investigating first-line systemic treatment for locally advanced or metastatic pancreatic cancer to identify baseline characteristics and prognostic variables. We created a structured overview showing the reporting frequencies of baseline characteristics and the prognostic relevance of identified variables. We used a modified Delphi panel of two rounds involving an international panel of 23 leading medical oncologists in the field of pancreatic cancer to develop a consensus on the various variables identified. In total, 39 randomised controlled trials that had data on 15 863 patients were included, of which 32 baseline characteristics and 26 prognostic characteristics were identified. After two consensus rounds, 23 baseline characteristics and 12 prognostic characteristics were designated as mandatory for future pancreatic cancer trials. The COnsensus statement on Mandatory Measurements in unresectable PAncreatic Cancer Trials (COMM-PACT) identifies a mandatory set of baseline and prognostic characteristics to allow adequate comparison of outcomes between pancreatic cancer studies.